Establishing an Integrated Permanent Sea-Level Monitoring Infrastructure towards the Implementation of Maritime Spatial Planning in Cyprus - Danezis, Chris; Nikolaidis, Marios; Mettas, Christodoulos; Hadjimitsis, Diofantos G.; Kokosis, Georgios; Kleanthous, Chrysanthi (My University, 2020)
The Maritime Spatial Planning is a piece of legislation (2014/89/EU) of the European Union that must be implemented by all member countries to enable management of their waters in a more coherent way to reduce conflicts, encourage investments, increase cross-border cooperation and protect the environment. Cyprus and Greece are working together in the frame of the THALCHOR2 project to implement this directive. From the Cyprus point of view, this directive has been a unique opportunity to modernize its Hydrographic and Geodetic Infrastructure to enable and facilitate the generation of reliable marine geospatial information. Concordantly, a network of integrated state-of-the-art multi-sensor stations has been established along the shoreline of the government-controlled territories to seamlessly monitor sea level, vertical crustal motion and meteorological parameters. This research provides insight into the implementation of this infrastructure and the data processing workflow to determine tidal levels. Furthermore, the first results acquired after exploiting two years of observations are presented along with initial aspects concerning mean sea-level variability in the Southeastern Mediterranean region.
Keywords: mean sea level; Cyprus; tidal data; tide gauge; marine spatial planning